Knowledge on Unsafe Abortion among Adolescent Students of Sarbamangala Secondary School, Kavre - Kafle, Bishnumani (Rupantaran: A Multidisciplinary Journal, 2023)
Unsafe abortion is a major health risks for women of the reproductive age group and is also a critical issue among adolescence. Due to lack of knowledge, awareness and lack of resources adolescents are facing problems. The objective of the study was to assess the knowledge regarding unsafe abortion among adolescent students. A descriptive study was carried out among adolescent students of Sarbamangala Secondary School of Kavrepalanchowk district, Nepal. After taking consent, 114 adolescents were selected from grade 9 to 12, purposively and self-administered questionnaires were distributed to them. Gathered data were accomplished through simple mathematical and descriptive way. Among 114 respondents, just more than half (52.2%) of the respondents were male and near about half (47.8%) of respondents were female. The respondents from grade 9 to 12 were 30.2%, 35.4%, 22.1% and 12.3% respectively and all most of all respondents (97.8%) were unmarried. The study reveals that only 34.2% of them had understood the meaning of unsafe abortion. Majority of respondents (78.5%) had inadequate knowledge, 20.2% respondents had moderate knowledge and few respondents (1.3%) had adequate knowledge regarding the unsafe abortion. This study concludes that there is lack of knowledge regarding abortion, legalization of abortion, unsafe abortion and its consequences among adolescent students of rural area. Awareness program on abortion can be conducted among the adolescent students to prevent unsafe abortion.